2001
DOI: 10.1159/000056082
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic Acid Influences the Respiratory Parameters of Rat Heart Mitochondria

Abstract: In the present study the effect of L-kynurenine, kynurenic acid and quinolinic acid on the heart mitochondrial function were investigated. Mitochondria were incubated with saturating concentrations of respiratory substrates glutamate/malate (5 mmol/l), succinate (10 mmol/l) or NADH (1 mmol/l), with and without kynurenines. The concentration of kynurenines varied between 1.25 µmol/l and 10 mmol/l. From all investigated kynurenines, only kynurenic acid affected dose-dependently the respiratory parameters of hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
3
26
2
1
Order By: Relevance
“…This is in agreement with previous reports showing that cellular respiration is altered by kynurenines (Baran et al, 2001(Baran et al, , 2003 and possibly explain the mechanisms by which the metabolites affect the mitochondrial respiration.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previous reports showing that cellular respiration is altered by kynurenines (Baran et al, 2001(Baran et al, , 2003 and possibly explain the mechanisms by which the metabolites affect the mitochondrial respiration.…”
Section: Discussionsupporting
confidence: 93%
“…This is interesting since some enzymes that catalyze the kynurenine pathway are located in the inner membrane of the mitochondria or inside this organelle, implying that kynurenines may have a direct and/or an indirect effect on the mitochondrial bioenergetics (Brown, 1971;Okamoto, 1971;Bender and McCreanor, 1982). Baran et al (2001) demonstrated that kynurenic acid (KA) affected dose-dependently the respiratory parameters of heart mitochondria, reducing significantly the respiratory control and P/O values. Furthermore, 3HK and 3HA lowered the respiratory control index and the ADP/oxygen ratio in the presence of glutamate/malate and succinate, while anthranilic acid (AA) reduced state III oxygen comsumption rate and lowered the respiratory control index only of glutamate/malate-respiring heart mitochondria (Baran et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the observed changes may be also a result of the KYNA effect on cancer cell metabolism. Previous studies revealed that KYNA decreased ATP synthesis in the presence of glutamate and malate in mitochondria isolated from rat heart (Baran et al 2001). …”
Section: Discussionmentioning
confidence: 91%
“…The toxicity of KYNA reported by other authors differed, depending on the used cell model, although the level of toxic concentrations was always higher by a few hundred-or even a few thousand-fold than values of KYNA detected in the human organism during the course of an inflammatory process. The adverse influence of KYNA on functions of the rat's myocardial mitochondria was observed at the concentrations of 125 μM -10 mM/l (Baran et al 2001), whereas the proliferation of endothelial cells in the bovine aorta was decreased (by 25%) at the concentration of 1 mM (Wejksza et al 2009). The mixed culture of rainbow trout lymphocytes employed in our study was characterized by a yet lower sensitivity to the adverse effect of high KYNA concentrations.…”
Section: Discussionmentioning
confidence: 95%